TAHAP PENGUASAAN TERHADAP KOMPONEN MASAKAN DALAM KALANGAN PELAJAR PENDIDIKAN KHAS MASALAH PEMBELAJARAN - Ali, Azita; Zawawi, Zaiton Abdullah (Online Journal for TVET Practitioners, 2018)
The purpose of this research is to study the perception of Special Education in Learning Problems students towards the subject Component Cuisine. The study has been conducted in SekolahMenengahTengkuPanglimaPerangTengku Muhammad Kuantan Pahang. In order to achieve all the objectives, questionnaire has been distributed to the 30 respondents. All the data that obtained from the questionnaire has been analyzed into frequency, percentage and mean score by using Winstep 3.69.11. The first objective of this research used the crosstab data analysis shows the mean score 4.846 which indicate the high level and prove that the respondents interested in learning the Life Skills. While in the aspects of respondent’s understanding towards the subject that teach by their teacher also shows a high level with the mean score 4.366 and indirectly achieve the second objective. From the study on the third objective, it shows a mean score 4.28 which indicate the high level of respondents application in practicing the subject skills into their life. The conclution of respondents have applied the practical skills in the subject at home and it is suggesting those Special Education teachers who teach the Life Skills subject to be more attentive towards their students.